Examen Especial a la Cuenta Remuneraciones del Personal Operativo de la Empresa C.A. Ecuatoriana de Cerámica, Periodo 2022 - Mónica Fernanda, Yaulema Cepeda (2024)
ABSTRACT: This research work was developed to carry out a special examination of the remuneration account of the operational staff of the company “C.A. Ecuatoriana de Cerámica”, period 2022. The methodology used in this research process is based on the deductive method, the type of research was documentary and field, with a non-experimental design, a quantitative approach, and a descriptive level of research; The population was composed of 16 documents; The techniques used were observation, interview, survey, and documentary review; The instruments used include the observation sheet, interview guide, questionnaire and recording sheet. The results highlight the existence of balanced internal control and the deficiency in the calculation of social benefit provisions. Therefore, it is concluded that after carrying out the special examination of the remuneration account of operational personnel for the period 2022, through an exhaustive and systematic review, the following findings were identified: ignorance of the regulations and lack of training were identified, It will be verified that the company does not have an updated database of operational personnel, the lack of a formal process for the management of complaints, deviations in the calculation of provisions and variations in direct and indirect labor accounts will be detected.